2020
DOI: 10.7203/leeme.46.16999
|View full text |Cite
|
Sign up to set email alerts
|

Una propuesta metodológica para trabajar la violencia de género con adolescentes a través de las canciones

Abstract: En nuestra sociedad las cifras de agresiones machistas aumentan entre la población adolescente a pesar de los esfuerzos realizados desde las administraciones para erradicar la violencia de género. Este trabajo de investigación centra su análisis en el discurso musical que rodea al adolescente para poder establecer una relación entre la presencia de mensajes machistas en los contenidos culturales y la normalización de estos comportamientos en sus pautas de interacción social. Para alcanzar nuestro objetivo, en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…For instance, a link between preference for listening to sexist songs and sexist attitudes was found (Saldarriaga et al, 2023). Other works have highlighted that songs fostering violence are more spread among adolescents in many contexts (Ruiz, 2020) and even very little children are exposed to sexist songs according to research carried out in the field of education (Chao-Fernández et al, 2020) In addition, and related to what the previous chapter has shown about the CDD, highly sexist songs can become a booster of the social status of the singers (Eze, 2020). Sexist and violent songs are also linked to a form of socialization of young people (Hormigos- Ruiz, 2023).…”
Section: Beauty and Ugliness In Music: Where Does Predatory Capital G...mentioning
confidence: 97%
“…For instance, a link between preference for listening to sexist songs and sexist attitudes was found (Saldarriaga et al, 2023). Other works have highlighted that songs fostering violence are more spread among adolescents in many contexts (Ruiz, 2020) and even very little children are exposed to sexist songs according to research carried out in the field of education (Chao-Fernández et al, 2020) In addition, and related to what the previous chapter has shown about the CDD, highly sexist songs can become a booster of the social status of the singers (Eze, 2020). Sexist and violent songs are also linked to a form of socialization of young people (Hormigos- Ruiz, 2023).…”
Section: Beauty and Ugliness In Music: Where Does Predatory Capital G...mentioning
confidence: 97%
“…Este trabajo pretendía analizar la representación de género a partir de una de sus expresiones musicales más presentes en la adolescencia, el RG, para poder sugerir propuestas en el marco de la educación musical. Es lógico que los docentes vean en el RG un recurso motivador, inclusivo y de empoderamiento para sus clases en secundaria (González y otros, 2016), que acerque la vida escolar a la realidad de los alumnos, pero debemos ser conscientes del peligro de su carga discriminatoria simbólica implícita y explícita que conlleva, sobre todo a raíz de sus letras, teniendo en cuenta que los contenidos que potencian la violencia de género son los más distribuidos por las industrias culturales y, por tanto, los que más éxito tienen entre los jóvenes (Hormigos, 2020) y que escuchar la agresión en la música se asocia con un aumento de la agresión y una disminución del comportamiento prosocial entre los oyentes adolescentes (Coyne y Padilla-Walker, 2015).…”
Section: Conclusionesunclassified